Photonic probes of surfaces - Halevi, P. (Peter) (Electromagnetic waves, 1995)
This volume is devoted principally to optical spectroscopies of material surfaces and also encompasses scattering techniques and theoretical response analysis as well as spectroscopies. In addition to solid surfaces some attention is also devoted to interfaces between two solids, between a solid and a liquid and to a liquid-vapor interface. These "surfaces" may be clean and perfect, in which case the purpose of the spectroscopical method at hand is to determine the deviation of the atomic structure in the surface region from that in the bulk, namely the "surface reconstruction." Otherwise the surface may be imperfect due to roughness, strain or overlayers, in which case the spectroscopy can yield information on the nature of such imperfections, including the monitoring of growth processes. One of the foremost purposes of surface spectroscopies is to extract information on atomic and molecular adsorbates on solid surfaces. Most of the 10 chapters are concerned with photonic sources of excitation, the respective spectral regions ranging from the far infrared to X-rays. In conclusion this book provides a state-of-the-art review of all major types of photonic probes of surfaces and interfaces and deals with both applications and experiment and theory